Oblivion - Cruise, Tom, 1962-; Freeman, Morgan; Leo, Melissa; Miranda, Claudio; Francis-Bruce, Richard; Kurylenko, Olga, 1979-; Riseborough, Andrea, 1981-; Coster-Waldau, Nikolaj, 1970-; Kosinski, Joseph, 1974-; Gajdusek, Karl.; Arndt, Michael D.; Chernin, Peter, 1951-; et al. (İstanbul : Yeni Film (distribution), 2017)
Jack Harper is the lone security repairman stationed on a desolate, nearly ruined future Earth. When he rescues a beautiful stranger from a downed spacecraft, her arrival triggers a nonstop chain of events that forces him to question everything he knows, and leaves humanity's fate in his hands.
Based on the graphic novel by Joseph Kosinski.
Based on the graphic novel by Joseph Kosinski.
Originally released as a motion picture in 2013.
Director of photography, Claudio Miranda; editor, Richard Francis-Bruce; music by M83.
Directed by, Joseph Kosinski ; screenplay by, Karl Gajdusek, Michael DeBruyn ; produced by Peter Chernin ... [et al.].Director of photography, Claudio Miranda ; editor, Richard Francis-Bruce ; music by M83.
Tom Cruise, Morgan Freeman, Melissa Leo, Olga Kurylenko, Andrea Riseborough, Nikolaj Coster-Waldau.
Keywords: Action and adventure films; Science fiction films; Feature films; Rescues -- Drama; Waste lands -- Drama; Interplanetary voyages -- Drama; Fiction films; Video recordings